Government Ethics - Ausín, Txetxu (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
Governments have a political dimension with ethical implications in both of them, the organization and the agents acting on it. This framework develops the basic principles of the activity within the governments and indicates and evaluates the tools for analyzing and balancing their responsibility.